Catalyst layer at the junction of a forward bias bipolar membrane for CO2 electrolysis - Matthieu Dessiex; Vincent Plouzennec; Sophia Haussener; Felix N. Büchi (Journal of Power Sources Advances)
CO2 reduction in an electrolysis cell with a forward bias bipolar membrane (BPM) ensures good selectivity and CO2 utilization, but still suffers from large overvoltages. Recent studies have shown that integrating metal-oxide catalysts at the BPM junction in reverse bias significantly enhances the performance of water electrolyzers. It remains unclear if this method has the same positive effect on CO2 electrolysis. We studied the performance of a specially designed zero-gap BPM CO2 electrolyzer operating in forward bias mode, incorporating metal-oxide nanoparticles at the BPM interface. For TiO2 catalyst, the optimal loading at the BPM junction was between 10 and 30 μgcm-2, resulting in a 75% higher current density for the same iR-free overpotential. Physical characterization using scanning electron microscopy of the catalyst layers revealed that the optimum performance of the CO2 electrolyzer correlates with a complete coverage. SiO2 and IrO2 metal-oxides were also tested at the BPM junction. SiO2 showed comparable performance to TiO2, whereas IrO2 improved the current density by approximately 100% at an iR-free overpotential of 0.7 V compared to the pristine BPM.